Aposentados do INSS : sua relação com o microcrédito e a educação financeira em bancos privados de varejo - Fontolan Junior, Moacir (2019)
Although the role of the elderly in our society and in the consumer market is gaining more and more relevance, the meanings attributed to this phase of life are conflicting, ranging from disability to an active role in the labor market. INSS retirees, because they have a stable and permanent income, are especially important for their families, companies and banks in particular, since to receive their benefit they become compulsory clients of these institutions. This relationship with the banks associated with the desire of many of these elderly people to remain active in the labor market led us to define as objectives of this work the understanding of their relationship with microcredit, a possible promoter of entrepreneurship; and with financial education, such as to increase financial knowledge and reduce the vulnerability of this public in relation to banks; as well as the influence of both on the relationship of these consumers with banks. In order to achieve these objectives, located at the confluence between the Transformative Consumer Research (TCR) movement and the Corporate Social Responsibility (CSR) actions, an exploratory research was used, with a qualitative approach, using documentary research and in-depth interviews (with managers and consumers) for the data collection, whose treatment consisted of a qualitative interpretation based on the tool of content analysis. The analysis of the results did not allow us to verify by the banks a recognition of this public as possible entrepreneurs or even as people still with the probability of a productive participation in the society. Retirees, on the other hand, do not recognize microcredit and financial education as tools to support entrepreneurship, even though they unanimously consider work as fundamental to their lives. Findings that indicate to banks the need for recognition of a new role for the elderly in society, associated with the expansion and revision of their financial education initiatives and a review of the offer and sale of microcredit, especially with the retired public.